Análise da relação entre depressão e hábito tabagista na metilação do gene BDNF - Quaioto, Bárbara Risse (2021)
Depression is one of the most common diseases between the cause of global inability, with millions of people affected. It is a heterogeneous and complex disease, which involves several risk factors. Although there is no single theory to explain its development, studies suggest a relationship with lower levels of brain derived neurotrophic factor (BDNF). In this sense, BDNF gene methylation, influenced by environmental factors, may be involved. It is known that individuals with depression are frequently smokers and it has already been demonstrated that changes in BDNF protein levels can occur due to tobacco use. However, the investigation of tobacco effect on BDNF gene methylation has not yet been investigated. Thus, the aim of this study was to evaluate the relationship between depression, smoking and BDNF gene methylation levels. To that end, a cross-sectional study was carried out with individuals assisted by the SUS primary health care network in the municipality of Alegre – ES. Data collection was performed using a socioeconomic, health and lifestyle assessment questionnaire, as well as anthropometric and depression assessment, using the Beck Depression Inventory-II (BDI-II). In addition, blood was collected for genomic DNA extraction and posterior methylation analysis. According to the Poisson regression, the highest prevalence of depression in the sample was explained by the female gender, not having a marriage bond, lack of leisure activities, smoking and BDNF methylation. Mann-Whitney and Generalized Linear Model analysis showed that depressed patients had higher levels of methylation, as well as non-smokers. As demonstrated by the Kruskal-Wallis test, followed by Dunn's posthoc test, smoking habit reduces BDNF methylation levels in depressed individuals, but not in non-depressed individuals. These results provide support for depression prevention policies. Furthermore, the data contribute to the understanding of the pathophysiology and diagnosis molecular of depression, involving the BDNF gene. Additionally, the results expose the need to assess the influence of smoking habit in studies on epigenetic changes in depression.